Analisis Kelayakan Snorkelling Kawasan Wisata Alam Pulau Kelagian Besar, Kecamatan Padang Cermin Kabupaten Pesawaran, Provinsi Lampung - Agus Setiawan (Journal of Tropical Marine Science, 2022)
The feasibility of an area is an important measure to determine its suitability as a tourist area. To determine the value of the suitability index of Kelagian Besar Island as a snorkeling tourism object, research has been carried out using snorkelling area suitability analysis method. The sampling location point is determined by considering the locations that are often used by tourists to swim. Data collection was carried out through direct observation and measurement in the field. The research results were processed using mathematical calculations and analyzed descriptively to determine the suitability class of the area for snorkeling activities. The criteria for the suitability of marine waters as a snorkelling tourism object refers to the criteria proposed by Yulianda (2007). Based on the results of the study, it was found that Kelagian Besar Island is very suitable to be used as a snorkelling tourist spot with a very suitable category (SS). Apart from physical factors, what attracts tourists to snorkel here is the expanse of coral reefs and the types of fish. In order to increase the number of visitors, local governments, both district and province, can carry out promotions.